Preservation solutions for static cold storage of kidney allografts: A systematic review and meta-analysis - O'Callaghan, J; Knight, SR; Morgan, R; Morris, P (2012)
Static cold storage is the most prevalent method for renal allograft preservation. Several solutions have been designed to counteract the detrimental effects of cold ischemia and reperfusion. The aim of this study was to appraise the evidence for the currently available preservation solutions. We performed a systematic literature search using MEDLINE, EMBASE, the Cochrane Library, the Transplant Library and trial registries. Inclusion criteria specified any comparative, prospective study for deceased donor renal allografts. Studies were assessed for methodological quality. The primary outcome was delayed graft function (DGF). Fifteen trials with a total of 3584 kidneys were included. Eurocollins was associated with a higher risk of DGF than University of Wisconsin solution (UW) in two randomized controlled trials (RCTs) and histidine - tryptophan - ketoglutarate (HTK) in two RCTs. UW was associated with an equal risk of DGF compared with Celsior in three RCTs and HTK in two RCTs. There was limited data regarding other comparisons and outcomes. The choice of preservation solution has an effect on the incidence of DGF, which might, in turn, affect long-term outcomes. Both UW and HTK have lower rates of DGF than Eurocollins. There is no difference in the incidence of DGF with the use of Celsior, HTK and UW. These findings are supported by registry data. © Copyright 2011 The American Society of Transplantation and the American Society of Transplant Surgeons.